Preparation and Study on Nitrogen- and Phosphorus- Containing Fire Resistant Coatings for Wood by UV-Cured Methods - Ma, Guoru; Wang, Xuan; Cai, Wei; Ma, Chao; Wang, Xin; Zhu, Yulu; Kan, Yongchun; Xing, Weiyi; Hu, Yuan (Frontiers in Materials, 2022)
Wood has been widely used since ancient times due to its biodegradable, good elas-ticity, impact resistance and easy availability. However, the flammability of wood has vastly limited its applications and the fire hazard of wood has cost a great loss of life and property. Thus, it is significant to improve the fire resistance of wood. Here, we used a phosphate acrylate monomer (PGMA) which was synthesized with phosphoric acid and glycidyl methacrylate by ring-opening reaction and melamine acrylic ester (MAAR) to make up a series of fireproof coatings with different proportions, and the fire resistance of wood has been investigated by limiting oxygen index (LOI) test, back temperature test and cone calorimeter test. When the wood was coated with the composite of 33.3% PGMA and 66.7% MAAR, the total heat release value decreased from 39.0 to 38.2 MJ/m2, and the total smoke release value decreased from 622 to 512 m2/m2, showing a remarkable improvement in fire resistance and smoke suppression. Thus, this easily prepared, cheap and effective flame retardant coating can promote a wider application of wood.